Synthesis and Electrochemistry of 1,2,4-Triferrocenylbenzene - Mei-Hua, Luo; Li-Min, Han; Quan-Ling, Suo; Guang-Bin, Zhang; Quan-Sheng, Liu (Asian Journal of Chemistry, 2010)
1,2,4-Triferrocenylbenzene (TFB) was synthesized by the [Co2(CO)6(μ2,h2-ferrocenyl acetylene)]catalyzed cyclization reaction of ferrocenyl acetylene. The molecular structure of 1,2,4-triferrocenylbenzene was determined by X-ray single crystal diffraction. The position selectivity of ferrocenyl was interpreted by K-Hübel's mechanism. The electrode reaction behaviours were demonstrated by cyclic voltammetry and microelectrode chronoamperometry.